Instalação e configuração de central IP - Lima, Fabio Augusto Nicolas e (2013)
The objective of this file is to present how to install and configure the Central Aastra MX-ONE. The plant has a communication system based on SIP protocol that provides voice communications combined with a variety of applications that offers guests a full range of unified communications and mobility. It is a system of IP communications. The flexibility to meet the specific communication needs and provides users with the right services, wherever they are using a phone of your choice. Since voice, data, video, all converge on a data network - public or private, fixed or mobile, you can access all the functions of his office, such as presence management applications and phone services, as well as managing the your calendar and phonebook.